Unveiling the Practice of Religious Moderation: A Case at a High School in Central Kalimantan, Indonesia - Muthia Farida; Ervantia Restulita L. Sigai; I Wayan Sindia Griya Danika; Budi Purnomo (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
The diverse background of Indonesian makes religious moderation and tolerance are the essential aspects in keeping the unity of the nation. This study aims to describe the practice of religious moderation in a public school in Pulang Pisau Regency, Central Kalimantan, Indonesia. This was a case study at SMAN 1 Pulang Pisau. The main informant was the school principal. A Semi-structured in-depth interview and documentation were conducted to help the researchers collected the data. Data analysis was carried out through data transcription, data reading, data reduction, data presentation and interpretation, and drawing conclusions. The results of this study indicate that the practice of religious moderation has actually existed long before the government proclaimed the term ‘religious moderation’. The principal has carried out several programs to implement this religious moderation. The first, the school has allowed the prayer recital at the flag assembly were led by the representative of each religious believers in turn every Monday morning. Second, the school has set the immersive religion activities for every religious believers in the school by seizing the moment of Pesantren Ramadhan week. Thus, this was not an obligatory for the Muslims only to practice religious activities, but also Hindu and Christian students and teachers could also set their own religious activities during the week. In addition, students and teachers were very tolerant to one another. This study provides suggestions for further research in order to be able to observe schools from various levels and formal/non-formal to investigate the practice of religious moderation in the educational environment. Keywords : religious moderation, tolerance, school, education